EKSTERYTORIALNE STOSOWANIE PRAWA OCHRONY KONKURENCJI - Molski, Rajmund (Wydział Prawa i Administracji UAM, 2002)
The practice of extraterritorial law enforcement in the era of globalisation is becoming more and more frequent and is invariably accompanied by controversy. This practice is often perceived as a threat to the national interest or even a violation of a given country’s sovereignty. Initially, any form of national law enforcement abroad was treated as an act of inadmissible violation of the other nation’s independence. Nowadays, the idea o f extraterritorialism is relatively broadly accepted or at least tolerated, although any acts of aggressive abuse o f this legal construct is inevitably met with fierce opposition and concern. The article covers the methods of extraterritorial application of competition law in America, the European Union, and Poland.
EXTRATERRITORIAL ENFORCEMENT OF COMPETITION LAW